The broken truth - Wortham, Reavis Z. (Tucker Snow thrillers, 2024)
"Special Agent Tucker Snow knows there's big money roaming the fields under the wide Texas sky--and the cattle rustlers committing largescale thefts on remote ranches know it, too. But when a prominent local rancher dies unexpectedly and his property is quietly sold to an unknown buyer, Tucker suspects there's something more sinister going on in his jurisdiction than the usual steal-and-resell racket. Still raw after the tragic death of his wife and young daughter, the lawman can't bear the thought of more innocent lives destroyed by people whose greed poisons everything around them. Working alongside his brother, Harley, Tucker uncovers a dark ring of organized crime that goes well beyond cattle rustling--a breed of deception and greed that has turned into a silent killer and will take down anyone who crosses its path. The question is whether Tuck and Harley will be able to shut it down before it finds the people they love the most..."--